The –514 polymorphism in the hepatic lipase gene (LIPC) does not influence androgen-mediated stimulation of hepatic lipase activity - Gloria Lena Vega; Jimin Gao; Thomas P. Bersot; Robert W. Mahley; Richard Verstraete; Scott M. Grundy; Ann White; Jonathan C. Cohen (Journal of Lipid Research, 1998)
The –514T allele of hepatic lipase is associated with increased high density lipoprotein-cholesterol levels in men, but not in women. This observation suggests that the –514C to T polymorphism may diminish the response of hepatic lipase to androgens. To test this hypothesis, five –514T and five –514C homozygous men were treated with the anabolic steroid stanozolol for 6 days. The mean increase in hepatic lipase activity was similar in the two groups (45 ± 10 vs. 51 ± 10 mmol·hr-1·l-1, P = 0.5). To evaluate the association between the –514 polymorphism and hepatic lipase activity at different physiological androgen concentrations, hepatic lipase genotypes and activities were measured in 44 men and 40 premenopausal women. The effect of the –514T allele on hepatic lipase activity was significant and quantitatively similar in both sexes. These data indicate that the –514 polymorphism does not influence the response of hepatic lipase activity to androgens, and that the effects of this polymorphism on hepatic lipase activity are independent of androgen action.—Vega, G. L., J. Gao, T. P. Bersot, R. W. Mahley, R. Verstraete, S. M. Grundy, A. White, and J. C. Cohen. The –514 polymorphism in the hepatic lipase gene (LIPC) does not influence androgen-mediated stimulation of hepatic lipase activity. J. Lipid Res. 1998. 39: 1520–1524.